Anagram Game to Teach Vocabulary Mastery for Islamic Junior High School Students - Mutiah, Wardah; Harida, Eka Sustri; Oktapian, Ardi (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research has investigated the students’ vocabulary mastery using Anagram for the Islamic Junior High School students in Padangsidimpuan. It was done through experimental method with pre-test and post-test design, with multiple choice test. There was 39 students as experimental class as the sample of this research, and mean-score was used to analysis the data in this research. After getting the data, the mean score of pre-test result is 51.72 and after using Anagram became 62.09. It can be said that anagram game has given good effect to the students’ vocabulary mastery of the VII grade students of the Islamic Junior high school students.